The Effect of Smart Hospital Implementation on Operational Efficiency and Physiotherapy Patient Satisfaction: A Literature Review - Mohamad Reza Hilmy; Erlina Puspitaloka Mahadewi; Fera Gusmi Nurba; Alika Shameela (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Digital transformation has been crucial to the evolution of healthcare organizations, with most hospitals in Asia having launched smart hospital initiatives to enhance service quality and operational efficiency. However, a significant gap remains, as there is still no established model demonstrating that smart hospital implementation contributes to operational efficiency and patient satisfaction, as described above. Objective: This study aims to examine the implementation of affordable smart hospitals, operational efficiency, and patient satisfaction related to physiotherapy as a healthcare service highly dependent on direct contact and intensive physical therapy sessions. Methods: We performed a systematic literature review (SLR) in accordance with the PRISMA protocol, including articles published between 2020 and 2026. A total of 25 articles were included in the synthesis through narrative analysis, and themes were identified across the literature. Results: Smart hospitals, in combination with hospital information systems, electronic medical records, and telemedicine, have been found to improve operational efficiency. This improvement leads to faster service processes, higher levels of accuracy in data entry by medical professionals, better resource optimization, and ultimately greater patient satisfaction due to reduced waiting times and improved quality of service interactions. Conclusion: Computing technology is a promising mechanism for maintaining process standards across all forms of operational performance, particularly in the domain of patient-centered care services primarily represented in physiotherapy settings. This study supports the use of such technologies to enhance patient comfort and operational robustness.